Implementation of good governance principles in village government context in Bantul Regency, Yogyakarta: Good Governance - Hilda Octavana Siregar; Siti Muslihah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This study aims to determine the application of good governance principles of the village government in Bantul Regency, Yogyakarta. In Indonesia, village is the lowest level government. The method used in this study was descriptive statistics with data from all villages in Bantul Regency. This study concluded that the implementation of good governance in villages in Bantul was generally good. Good governance indicators have been implemented by more than 50% of all villages even though some indicators still need to be improved. The villages have applied the good governance principles in accordance with the international formulation, namely, efficiency and effectiveness, openness and transparency, innovation, long-term orientation, reliable, and accountable financial management. The implementation can be strengthened through training to the village government and communities, especially regarding innovation and long-term orientation principles that must be possessed so that the villages can become more independent and develop more rapidly.